Віруси у продуктах харчування - Скроцька, Оксана Ігорівна; Волошина, Ірина Миколаївна; Кістенюк, Т. С. (My University, 2014)
Розглянуто шляхи потрапляння вірусів до харчових продуктів та методи їх виявлення. Показано, що віруси стійкі до несприятливих умов навколишнього середовища та можуть упродовж декількох місяців зберігатися у харчових продуктах та довкіллі. Наведено дані щодо виявлення у продуктах харчування ентеровірусів, поліовірусів, ротавірусів, вірусу холери свиней (HCV), вірусу африканської свинячої лихоманки (ASFV), вірусу ящура і ЕСНО-вірусу. The paths of viruses’ incorporation into the food have been reviewed. The methods of identification of viruses in the food by applying the sensitive cells and polymerase chain reaction technique have been provided. The benefits and disadvantages of the mentioned methods were outlined. The following human viruses were identified in the food: enterovirus, poliovirus, rotavirus, Coxsackie B5 virus, hog cholera virus (HCV), African swine fever virus (ASFV), FMD virus and ECHO-virus. The statistics data regarding frequency of viruses isolation form the food has been provided for Ukraine. It has been demonstrated that the viruses are resistant to adverse environmental conditions and can stay active for several months in food and environment. The following methods of viruses’ inactivation in the food were characterized: pH lowering, cooling and freezing, heating and UV exposure.
Keywords: кафедра біотехнології і мікробіології; віруси; харчові продукти; біобезпека; viruses; food; biosafety